The cytokine receptor CRLF3 is a human neuroprotective EV-3 (Epo) receptor - Knorr, Debbra Y.; Rodriguez Polo, Ignacio; Pies, Hanna S.; Schwedhelm-Domeyer, Nicola; Pauls, Stephanie; Behr, Rüdiger; Heinrich, Ralf (Frontiers in Molecular Neuroscience, 2023)
The evolutionary conserved orphan cytokine receptor-like factor 3 (CRLF3) has been implicated in human disease, vertebrate hematopoiesis and insect neuroprotection. While its specific functions are elusive, experimental evidence points toward a general role in cell homeostasis. Erythropoietin (Epo) is a major regulator of vertebrate hematopoiesis and a general cytoprotective cytokine. Erythropoietic functions mediated by classical Epo receptor are understood in great detail whereas Epo-mediated cytoprotective mechanisms are more complex due to involvement of additional Epo receptors and a non-erythropoietic splice variant with selectivity for certain receptors. In the present study, we show that the human CRLF3 mediates neuroprotection upon activation with the natural Epo splice variant EV-3. We generated CRLF3 knock-out iPSC lines and differentiated them toward the neuronal lineage. While apoptotic death of rotenone-challenged wild type iPSC-derived neurons was prevented by EV-3, EV-3-mediated neuroprotection was absent in CRLF3 knock-out neurons. Rotenone-induced apoptosis and EV-3-mediated neuroprotection were associated with differential expression of pro-and anti-apoptotic genes. Our data characterize human CRLF3 as a receptor involved in Epo-mediated neuroprotection and identify CRLF3 as the first known receptor for EV-3.